Cover Image. Issue 13 (29th October 2020) - Higuchi, Kohei; Chigira, Masahiro; Lee, Der‐Her; Wu, Jian‐Hong
Abstract : The cover image is based on the Original Article Simultaneous water and vapor transfer in an unsaturated mudstone in badlands terrain, southwestern Taiwan Simultaneous water and vapor transfer in an unsaturated mudstone by Kohei Higuchi et al., https://doi.org/10.1002/esp.4968 .